(3JNWjW GdEfJGL heQGbHJgs - (3eMeO GHOjhj(B, (3GdMSjfs ((3YeGf(B:s (3OGQ GdefGgL ddfTQ hGdJhRjY(B,s, 2004)
(3GdJfHD HGdWdH(B- (3JNWjW GdEfJGL(B- (3LOhdI GdEfJGL(B- (3GdQbGHI Ydi GdEfJGL(B- (3EOGQI GdeNRhf(B- (3fXGe JNWjW GdeSJdReGJ GdeGOjI(B- (3fXGe GdEfJGL GdBfj(B- (3GdQbGHI Ydi GdLhOIs
(3GdeQGLY U(B.231 (3cTGa eUWdMGJ U(B.234s
Keywords: (3GdEfJGLs; (3JNWjW GdEfJGLs; (3eQGbHI GdEfJGLs